Charge-ordering transition in (TMTTF)2X explored via dilatometry - De Souza, Mariano [UNESP]; Pouget, Jean-Paul (My University, 2013)
Charge-ordering phenomena have been highly topical over the past few years. A phase transition towards a charge-ordered state has been observed experimentally in several classes of materials. Among them, many studies have been devoted to the family of quasi-one-dimensional organic charge-transfer salts (TMTTF)2X, where (TMTTF) stands for tetramethyltetrathiafulvalene and X for a monovalent anion (X = PF6, AsF6 and SbF6). However, the relationship between the electron localization phenomena and the role of the lattice distortion in stabilizing the charge-ordering pattern is poorly documented in the literature. Here we present a brief overview of selected literature results, with emphasis placed on recent thermal expansion experiments probing the charge-ordering transition of these salts. © 2013 IOP Publishing Ltd.
Keywords: Charge ordered state; Charge-ordering transitions; Charge-transfer salts; Electron localizations; Lattice distortions; Monovalent anions; Quasi-one-dimensional; Tetramethyltetrathiafulvalene; Thermal expansion; Salts